FACTORS INFLUENCING AWARENESS AND ADOPTION OF CLIMATE CHANGE ADAPTATION STRATEGIES AMONG MAIZE FARMERS IN ADAMAWA AND TARABA STATES, NIGERIA - Dahiru, U. A.; Garba, M.; Abdullahi, S.; Idi, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the factors influencing awareness and adoption of climate change adaptation strategies among maize farmers in Adamawa and Taraba States, Nigeria. A multistage sampling technique was used to select 400 farmers and data were collected using structured questionnaires. Descriptive statistics were used to analyze the level of adaptation and constraints, while Logit regression used to assessed factors influence climate-change awareness. The findings indicated that farmers widely adopted strategies such as access to markets and value addition (????̅ = 4.0), climate-smart agricultural practices (????̅ = 3.8), crop diversification (????̅ = 3.7), and water-management techniques (????̅ = 3.6). However, adoption of innovative technologies (????̅ = 2.9), sustainable agricultural practices (????̅ = 2.9), and agroforestry (????̅ = 2.8) remained low. Results of the Logit model showed that educational level (P<0.01), household size (P<0.01), farm size (P<0.05), land-acquisition method (P<0.01), secondary occupation (P<0.01), and access to extension services (P<0.01) significantly influenced farmers’ awareness of climate change among maize farmers in the study area. The major constraints to awareness and adoption climate change were inadequate technical knowledge (82.6%), land-tenure challenges (82.1%), limited market access (79.6%), and sociocultural barriers (79.6%). The study concludes that education level, household size, farm size, land acquisition method and secondary occupation were the factors influencing awareness of climate change effect adaptation strategies among maize farmers in the study area. The study recommends the need by stakeholders to strengthen the extension systems, enhancing farmers’ technical capacity, improving land-tenure security, and expanding access to credit and infrastructure to improve climate resilience among maize farmers in the study area.